2015
DOI: 10.1111/ijfs.12918
|View full text |Cite
|
Sign up to set email alerts
|

Study of pulsed light inactivation and growth dynamics during storage of Escherichia coli ATCC 35218, Listeria innocua ATCC 33090, Salmonella Enteritidis MA44 and Saccharomyces cerevisiae KE162 and native flora in apple, orange and strawberry juices

Abstract: Summary The response of some inoculated strains and native flora to PL treatment (Xenon lamp, 3 pulses s−1, 10 cm distance from the lamp, 71.6 J cm−2) in apple, orange and strawberry fresh juices with different absorbance, turbidity and particle size was investigated. Microbial growth dynamics during 12‐day storage (5 °C) of PL‐treated juices was also evaluated. PL treatments provoked 0.3–2.6 log reductions for inoculated microorganisms and 0.1–0.7 for native flora. High turbidity and particles with high UV ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 42 publications
(73 reference statements)
2
27
0
Order By: Relevance
“…More than 5‐log reduction or complete inactivation of both AM and YM was obtained at the severe condition of 17.42 W/cm 2 fluence‐rate for 3 min (2,400 V/2.4 cm/3 min). Ferrario et al (2015) observed a poor lethality of AM (0.1–0.6 log reductions) and YM (0.5–0.6 log reductions) after PLT of fruit juices. However, the fluence values were too low compared to the current study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 5‐log reduction or complete inactivation of both AM and YM was obtained at the severe condition of 17.42 W/cm 2 fluence‐rate for 3 min (2,400 V/2.4 cm/3 min). Ferrario et al (2015) observed a poor lethality of AM (0.1–0.6 log reductions) and YM (0.5–0.6 log reductions) after PLT of fruit juices. However, the fluence values were too low compared to the current study.…”
Section: Resultsmentioning
confidence: 99%
“…PLT has recently gained interest regarding its effect mainly on microorganism inactivation in fruit juices from apple, melon, and strawberry (Ferrario, Alzamora, & Guerrero, 2013, 2015; Palgan et al, 2011). The extent of the inactivation of spoilage enzymes by PLT has been studied in model solutions (Manzocco, Panozzo, & Nicoli, 2013; Pellicer & Gómez‐López, 2017; Pellicer, Navarro, & Gómez‐López, 2018, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…UV-C is an environmental-friendly strategy for extending the shelf life of fresh-cut produce and has proved to be effective in reducing bacterial count but not damage other quality attributes [34][35][36]. Our results showed that UV-C treatment was effective in sterilization of fresh-cut potatoes during storage, and, more interestingly, the SAS treatment had a better effect than UV-C treatment during the early storage period.…”
Section: Discussionmentioning
confidence: 57%
“…Growth of microbial flora during storage of apple, orange and strawberry juices treated with pulsed light was prohibited (Ferrario et al . ).…”
Section: Introductionmentioning
confidence: 97%